Konsep Kurikulum Pendidikan Islam (Studi Komparatif Pemikiran Al-Ghozali dan Ibnu Miskawaih) - ., Nisrokha (Madaniyah, 2017)
This paper explore the thoughts of Islamic figures in the world of education, namely Al-Ghozali and Ibn Miskawayh, relating to his thoughts on Islamic Education Curriculum and its relevance to the current Islamic education. Approach to the study conducted using qualitative methods Library Research. The results show that the concept of curriculum Al-Ghazali in compiling the lessons more to give special attention to the sciences of religion and ethics as at doing it against the sciences that are beneficial to peoples lives. While the thought of Ibn Miskawayh more emphasis on moral education including one underlying concept in the field of education.